PERBANDINGAN PENGARUH PELATIHAN SENAM JANTUNG SEHAT SERI II DAN SENAM KESEGARAN JASMANI 2000 TERHADAP KEBUGARAN JASMANI - Muhammad Mulhim (Lambung Mangkurat University, 2014)
The Comparation of Improved Cardiovascular Health Part Two and Physical Fitness 2000 Gymnastics On Effect of Aerobic Endurance. Gymnastic Physical Fitness aims to increase the quality of the Indonesian health, and it is important part for developing human resurces, in tern of supporting the success of the Indonesian. Cardiovascular Health Part Two Activities is one of promotif-preventif and rehabilitatif activities for maintening the health of heart and improving the society health. By doing those activites, the participants do a set of exercises that have been organized in a package followed by a music, and designed nationally.Recently, in the field of sports medicient development it has been designed the newest gymnastics called Physical Fitness 2000 Gymnastics by Menpora office as the continuesing gymnastic physical fitness of there is a new product in sport fitness material, then the society tend to be owner of it. It means that the old one as thought unused properly, but the fact that the purpose of the sport physical material in order to provide aclonce in choosing it. Nevertheless, the gymnastic physical fitness should be tested through an experiment in order to know its advantage. It should be done by compacing it with Cardiovascular Health Part Two Activities, and hold to the basic principle of aerobic trainning. Source problems are proposed to in this research namely (1) is the Cardiovascular health Part Two Activities able to increase physical fitness ? (2) is the Physical Fitness 2000 Gymnastic able to increase physical fitness ? (3) is the Cardiovascular health Part Two Activities able to more increase physical fitness than that of Physical Fitness 2000 Gymnastic? To solve the above problems, the research is designed with experimental design “Randomize Pre Test Post Test Group Design” and it was carried in the school of health nursery at Martapura in acadymic year 2000/2001 on sample of 40 students out of 47 students in the population. The sample drawn with random sampling technique.Cardiovascular Health Part Two Activities by the experiment group 1 (K1), and Physical Fitness 2000 Gymnastic by the experiment group 2 (K2). To answer the problems proposed in the research in based on result of increament physical fitness score which is analysed by one way anova with 95 % level of significant level (α = 0,05). For experimental group 1 (K1) with Cardiovascular Health Part Two Activities, the F probability is 0,0000 while for the experimental group 2 (K2) with Physical Fitness 2000Gymnastic the F probability is 0,0000. Both of F values are less than α = 0,05 which means there is significance differences, whiles for compariting the effect of Cardiovascular Health Part Two Activities and Physical Fitness 2000 Gymnastic. The p- value was 0,4250 for the pre-test and 0,3518 for post-test. Both of the p-value for both treatment are not significant which means that Cardiovascular Health Part Two Activities is able to increase the physical fitness as good as Physical Fitness 2000 Gymnastic.Some conclusions can be drawned from the above results namely (1) Cardiovascular Health Part Two Activities is able to increase the physical fitness for students of school health nursery at Martapura. (2) Physical Fitness 2000 Gymnastic is able to increase the physical fitness for students of the school health nursery at Martapura. (3) Physical Fitness 2000 Gymnastic is able to increase the physical fitness as good as Cardiovascular Health Part Two Activities for students of the school health nursery at Martapura. Keywords: Cardiovascular Health Part Two Activities, Physical Fitness 2000Gymnastics, Aerobic Endurance.